Activation of nitric oxide synthase through muscarinic receptors in rat parotid gland - Rosignoli, Florencia (2002)
Muscarinic receptors play an important role in secretory and vasodilator responses in rat salivary glands. Nitric oxide synthase (NOS) activity was found coupled to muscarinic receptor activation as well as to nitric oxide-mediated amylase secretion elicited by carbachol. Parotid glands presented a predominant M3 and a minor muscarinic M1 acetylcholine receptor population, though carbachol stimulated NOS activity only through muscarinic M3 receptors as revealed in the presence of 4-diphenylacetoxy-N-methylpiperidine methiodide (4-DAMP) and pirenzepine. Amylase secretion induced by carbachol appeared to be partly mediated by nitric oxide and nitric oxide-induced signaling since N-nitro-L-arginine methyl ester (L-NAME) inhibited the effect as well as did methylene blue. A negative regulation of NOS by protein kinase C activation in the presence of a high concentration of carbachol was seen in parotid glands and this inhibition was paralleled by amylase secretion.